Musculoskeletal model of awkward carrying postures. Issue 1 (31st December 2016) - Abdul Majid, N.A.; Mohamaddan, S.; Omiya, T.; Notomi, M.
Abstract: Improper posture of carrying loads can cause low back disorders. This study investigates the impact of using a footstool in spinal force and muscle activity when: (1) pushing/pulling load farther/nearer from the body and (2) twisting the trunk while carrying load. A whole body musculoskeletal model carrying a light load of 5, 7.5 and 10 kg is developed and inverse dynamics analyzes are conducted. Electromyography activities are also recorded to compare to the results from analyzes. Analyzes demonstrated that using a footstool when carrying a light load can reduce the intradiscal compression force. The results from the analysis are found to be consistent with the electromyogram measurement. This study suggests that load should be positioned closer to the body and footstool of 5 cm height should be used to reduce spinal forces and muscle activity on the lumbar region.